Ballots and Bullets : The Elusive Democratic Peace - Gowa, Joanne S. (Book collections on Project MUSE., 2000)
There is a widespread belief, among both political scientists and government policymakers, that "democracies don't fight each other." Here Joanne Gowa challenges that belief. In a thorough, systematic critique, she shows that, while democracies were less likely than other states to engage each other in armed conflicts between 1945 and 1980, they were just as likely to do so as were other states before 1914. Thus, no reason exists to believe that a democratic peace will survive the end of the Cold War. Since U.S. foreign policy is currently directed toward promoting democracy abroad, Gowa's fi.